Створення та впровадження фреймворку для автоматичного тестування інфокомунікаційних додатків - Красніков, В. О.; Чеботарьова, Д. В. (ХНУРЕ, 2025)
This discusses the development and implementation of an automated testing framework for infocommunication applications. Automated testing significantly reduces testing time, enhances software stability, and minimizes human-related risks. The proposed framework integrates seamlessly into the development process, ensuring systematic and repeatable test execution. The study highlights the advantages of automation, including CI/CD integration, scalability, and efficient resource utilization. Additionally, it emphasizes the importance of selecting appropriate tools, such as Selenium or Appium, based on project requirements. The research underscores the strategic role of test automation in improving software quality and accelerating product release cycles
Keywords: впровадження фреймворку; тестування інфокомунікаційних додатків